Experimental and Theoretical Study on the “2,2′-Bipiridyl-Ni-Catalyzed” Hirao Reaction of >P(O)H Reagents and Halobenzenes: A Ni(0) → Ni(II) or a Ni(II) → Ni(IV) Mechanism? - Keglevich, György (J Org Chem, 2020)
[Image: see text] It was found by us that the P–C coupling reaction of >P(O)H reagents with PhX (X = I and Br) in the presence of NiCl(2)/Zn as the precursors for the assumed Ni(0) complexant together with 2,2′-bipyridine as the ligand took place only with PhI at 50/70 °C. M06-2X/6-31G(d,p)//PCM(MeCN) calculations for the reaction of Ph(2)P(O)H and PhX revealed a favorable energetics only for the loss of iodide following the oxidative addition of PhI on the Ni(0) atom. However, the assumed transition states with Ni(II) formed after P-ligand uptake and deprotonation could not undergo reductive elimination meaning a “dead-end route”. Hence, it was assumed that the initial complexation of the remaining Ni(2+) ions with 2,2′-bipyridine may move the P–C coupling forward via a Ni(II) → Ni(IV) transition. This route was also confirmed by calculations, and this mechanism was justified by preparative experiments carried out using NiCl(2)/bipyridine in the absence of Zn. Hence, the generally accepted Ni(0) → Ni(II) route was refuted by us, confirming the generality of the Ni(II) → N(IV) protocol, either in the presence of bipyridine, or using the excess of the >P(O)H reagent as the P-ligand. The results of the calculations on the complex forming ability of Ni(0) and Ni(II) with 2,2′-bipyridine or the P-reagents were in accord with our mechanistic proposition.